Phänologie und Populationsdynamik des Seehundes (Phoca vitulina) im Wattenmeer : Grundlagen zur Messung von Statusparametern - Abt, Kai F. (2002)
The harbour seal is a common species in the European Wadden Sea. However, in the 20th century the population declined dramatically due to over-hunting and did not commence recovery until the 1970s. In 1988, a virus epizootic caused another breakdown. To ensure conservation of a viable seal population, the countries adjacent to the Wadden Sea, Germany, Denmark, and the Netherlands, concluded on close cooperation in seal monitoring and management. Among the prospected results of coordinated census and research are estimates of seal vital parameters, such as rate of increase and mortality. The present study provides these parameters for various periods ofthe past population history, with focus on 1989-2000. Additionally, recommendations on concepts and methods in seal monitoring are given. Census data from all Wadden Sea areas and from Helgoland recorded between 1960 and 2000 were used to analyse harbour seal phenology and trends. Age- and sex-specific mortality and the influence of demographic change on apparent short-term population trends were investigated based on age data from 4700 dead seals. Required additional information on age-specific female fertility rates and age- and sex-specific haul-out frequencies was taken from the literature. The phenology of count results in 1989-2000 revealed to annual peaks, corresponding to the favourable times for synchronous survey of seals in all Wadden Sea areas. The first peak was in the third decade of June, coinciding with the late pupping season, whereas the second was in the first decade of August, when the maximum proportion of seals moult. There were differences in phenology between the inner German Bight and the peripheral Wadden Sea areas, which are explained by different average exposure times of seal haul-out sites. lt is suggested that the seasonal count data which are least influenced by tidal effects and thus are most comparable among different areas are those from the peak moulting season. In the 1990s, at least 95% of harbour seal births in the Wadden Sea ...